Translator, Emotions and Translation - Tokarz, Bożena (Poznańskie Studia Slawistyczne, 2015)
A translator, recreating the original, creatively stimulates her/his intellect, knowledge, senses and emotions. At the same time, s/he remains in agreement with the emotions presented in the original by assuming with respect to it the only ethically possible attitude, namely empathy. The presence of her/his own emotions in translation, such as sympathy or antipathy, is ethically unacceptable. Emotions occupy an important place in translation because of the difficulty regarding their linguistic transfer, interpretation of their function in the original, intercultural communication differences, and because of the attitude of the translator towards the original. Problems related to emotions concern the art of translation and the need for emotional detachment of the translator, who at the same time needs to maintain an empathic attitude towards the original. Emotions should be considered both on the internal level of the text (the original and the translation) and on the external one – the translator’s perspective.